2020
DOI: 10.1002/jclp.23096
|View full text |Cite
|
Sign up to set email alerts
|

Religiousness, meaning, and quality of life: Test of a mediational model among adults seeking a spiritually integrated inpatient program

Abstract: Objective Religious beliefs and practices may augment a sense of meaning in life that could support quality of life (QOL) in physical, social, and emotional domains amid mental health crises. However, these associations have not been thoroughly tested among persons with serious mental illness (SMI). Methods Focusing on 248 adults who had recently enrolled in a spiritually integrated acute psychiatric hospitalization program, we incorporated structural equation modeling to examine whether (1) religiousness woul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…We also did not assess the role of spirituality or other sources of meaning in our study variables (e.g., family, work). Therefore, despite the well-documented link between spirituality and meaning in life (e.g., Hinkel et al, 2021;Park, 2013), we cannot determine whether spirituality truly shaped patients' perceptions of meaning in ways that possibly led to less ultimate meaning struggles and greater flourishing in the treatment process. The time-limited nature of this program also restricted the interval between assessments; a varying pattern of temporal associations between meaning-related factors and mental health outcomes might emerge in outpatient settings that implement spiritually integrated interventions on a weekly or semiweekly basis over longer periods of time.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We also did not assess the role of spirituality or other sources of meaning in our study variables (e.g., family, work). Therefore, despite the well-documented link between spirituality and meaning in life (e.g., Hinkel et al, 2021;Park, 2013), we cannot determine whether spirituality truly shaped patients' perceptions of meaning in ways that possibly led to less ultimate meaning struggles and greater flourishing in the treatment process. The time-limited nature of this program also restricted the interval between assessments; a varying pattern of temporal associations between meaning-related factors and mental health outcomes might emerge in outpatient settings that implement spiritually integrated interventions on a weekly or semiweekly basis over longer periods of time.…”
Section: Discussionmentioning
confidence: 97%
“…Meta‐analytic findings from 66 studies also found that sanctification (i.e., a process by which aspects of life are perceived as having sacred value or divine character and significance) was positively linked with indices of positive mental health (e.g., flourishing) and inversely associated with negative mental health (e.g., depression symptoms; Mahoney et al, 2021). In addition, cross‐sectional findings with an earlier sample of patients in this spiritually integrated inpatient program revealed meaning in life fully accounted for the well‐established link between spirituality and quality of life (Hinkel et al, 2021). Yet, research has not examined the perceived presence of meaning in life as a facilitator or mechanism for clinical outcomes in inpatient programs that attend to spiritual and/or religious aspects of patients' lives.…”
Section: Introductionmentioning
confidence: 95%
“…Besides, it may be related to religious beliefs. As we know, Iran is a country with rich religious resources, beliefs and practices that may help patients to improve a sense of meaning in life (Hinkel et al, 2021). For self-esteem, sensitivity analyses showed that the heterogeneity was caused by Gong et al (2014) and Wang (2015).…”
Section: Discussionmentioning
confidence: 99%